2008
DOI: 10.1107/s0021889808011898
|View full text |Cite
|
Sign up to set email alerts
|

Absorption correction based on a three-dimensional model reconstruction from visual images

Abstract: The results are presented of a feasibility study for the application of absorption corrections to macromolecular crystallographic X‐ray diffraction data using a three‐dimensional crystal model generated photographically. The model allows path lengths through the crystal, the solvent and the crystal mount system to be determined. The approach has been tested on the macromolecular crystallography beamline ID23‐1 at the ESRF in Grenoble using a model insulin system with the standard mini diffractometer facilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…For the calculation of the absorption correction factors, the integral [equation (1)] is calculated over the crystal volume (Angel, 2004) as the only source of X-ray diffraction. To move from the continuous integral in equation ( 1) to a discrete equation, we replace crystal elements dV by crystal voxels �V from the tomographic reconstruction (Leal et al, 2008). This allows substitution of the integral over the volume V with a sum over the crystal voxels.…”
Section: Analytical Absorption Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the calculation of the absorption correction factors, the integral [equation (1)] is calculated over the crystal volume (Angel, 2004) as the only source of X-ray diffraction. To move from the continuous integral in equation ( 1) to a discrete equation, we replace crystal elements dV by crystal voxels �V from the tomographic reconstruction (Leal et al, 2008). This allows substitution of the integral over the volume V with a sum over the crystal voxels.…”
Section: Analytical Absorption Correctionmentioning
confidence: 99%
“…To analytically calculate absorption correction factors for a sample with irregular shape, its shape and orientation have to be characterized in detail. Previous work using optical microscopy to reconstruct a 3D model of the sample, containing crystal, sample mount and mother liquor, showed that absorption correction was viable and advantageous at lower levels of data multiplicity (Leal et al, 2008;Strutz, 2011). An alternative approach to obtain a 3D model of the sample is X-ray tomography, which has been applied to either characterize or visualize crystals (Merrifield et al, 2011;Warren et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Two methods have been described to overcome this problem. Leal et al (2008) and Strutz (2011) have shown that the three-dimensional model of a protein crystal, buffer and sample mount can be constructed using a series of twodimensional images (silhouettes) taken with an optical sample viewing system (microscope). The resulting model allows the determination of geometrical parameters for absorption correction, but the reconstruction is critically dependent on the image quality commanded by the sample transparency, depth of field, illumination, etc.…”
Section: Introductionmentioning
confidence: 99%